2019
DOI: 10.3390/nu11112731
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Contingency Reduces Alcohol Drinking by Altering Central Neurotransmitter Receptor Gene Expression in Rats

Abstract: We have previously shown that 6 weeks of intermittent high-fat diet (Int-HFD) pre-exposure significantly reduced alcohol drinking in rats, providing preliminary evidence of the effectiveness of a dietary intervention in reducing alcohol intake. However, the functional framework and underlying neurobiological mechanisms of such dietary intervention are unknown. Here, we examined the impact of Int-HFD pre-exposure duration on alcohol drinking, plasma feeding peptides, and central neurotransmitter receptors gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 63 publications
(80 reference statements)
4
22
0
Order By: Relevance
“…Again alcohol drinking was significantly reduced in the intermittent HFD exposed group of rats compared to the chow controls [54]. Using the similar paradigm, a more recent study from our lab has identified that intermittent HFD pre-exposure is critical to reducing alcohol drinking [55]. It is important to mention here that our studies utilized male adult rats, and it is unclear if similar results could be obtained in female rats.…”
Section: Non-human Studiesmentioning
confidence: 53%
See 2 more Smart Citations
“…Again alcohol drinking was significantly reduced in the intermittent HFD exposed group of rats compared to the chow controls [54]. Using the similar paradigm, a more recent study from our lab has identified that intermittent HFD pre-exposure is critical to reducing alcohol drinking [55]. It is important to mention here that our studies utilized male adult rats, and it is unclear if similar results could be obtained in female rats.…”
Section: Non-human Studiesmentioning
confidence: 53%
“…A recent study found no differences in the plasma feeding peptides in rats displaying reduced alcohol drinking phenotype following a binge/compensate HFD feeding [55]. In addition, gene expression of several neurotransmitter receptors was significantly altered in the striatum and VTA of rats displaying binge/compensate HFD feeding compared to the chow controls, whereas no such changes were observed in the amygdala and hypothalamus [55]. These data collectively argue against the involvement of peripheral systems and point towards central mechanisms, particularly brain reward regions, in mediating reduced alcohol drinking following binge-like HFD intake.…”
Section: Potential Neurobiological Mechanismsmentioning
confidence: 94%
See 1 more Smart Citation
“…However, intermittent exposure to an HFD for 6 to 7 weeks can either decrease (Sirohi et al, 2017) or increase (Coker et al, 2020) alcohol drinking, so it appears that additional variables are operational. Data from the studies discussed above supported the conclusion that the observed outcomes were attributed to alterations in neurotransmitter neurochemistry (Peleg-Raibstein et al, 2016;Villavasso et al, 2019), decreased anxiety and elevated ghrelin (Sirohi et al, 2017), and the development of insulin insensitivity and glucose intolerance (Coker et al, 2020).…”
Section: High-fat Dietmentioning
confidence: 71%
“…Offspring from dams exposed to an HFD throughout pregnancy and lactation showed increased alcohol drinking in adulthood (Peleg-Raibstein et al, 2016). Adult rats given access to an HFD on an intermittent schedule significantly decreased their alcohol drinking (Sirohi et al, 2017;Villavasso et al, 2019). Coker et al (2020) carried out an extensive analysis of the impact of HFD access schedules on alcohol drinking, and the results were very interesting.…”
Section: High-fat Dietmentioning
confidence: 99%